2011
DOI: 10.2131/jts.36.231
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depression by dihydropyrazine derivative

Abstract: -Dihydropyrazine (DHP), which is formed by nonenzymatic glycation, generates various radical species that lead to DNA damage and enzyme inhibition. In this study, we examined the reaction between DHP derivatives and glutathione (GSH). DHP exposure caused more intense growth inhibition of a GSH-deficient mutant Escherichia coli strain compared with the wild-type strain. DHP-exposed mouse fibroblasts showed a decrease in the cellular GSH level. The obtained data suggested that the reaction of DHP with GSH possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Despite concerns surrounding the effects of DHPs on human health, there is very little evidence in the literature regarding a causal relationship between DHP and disease. We previously reported that DHP causes greater growth inhibition in GSH-deficient bacteria than it does in GSH-sufficient bacteria (Takechi et al, 2011), and we also observed a significant decrease in the ratio of intracellular reduced glutathione and oxidized glutathione (GSH/GSSG) in DHP-exposed cultured cell (Ishida et al, 2012). In the current study, we have identified novel DHP-GSH adducts from the reaction products of DHP with GSH.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Despite concerns surrounding the effects of DHPs on human health, there is very little evidence in the literature regarding a causal relationship between DHP and disease. We previously reported that DHP causes greater growth inhibition in GSH-deficient bacteria than it does in GSH-sufficient bacteria (Takechi et al, 2011), and we also observed a significant decrease in the ratio of intracellular reduced glutathione and oxidized glutathione (GSH/GSSG) in DHP-exposed cultured cell (Ishida et al, 2012). In the current study, we have identified novel DHP-GSH adducts from the reaction products of DHP with GSH.…”
Section: Introductionsupporting
confidence: 53%
“…Given that GSH is converted to GSSG following its reaction with ROS, and GSH depletion results in elevated cytotoxicity (Mitchell and Russo, 1987). In our previous study, DHP caused growth inhibition of GSH-deficient bacteria (Takechi et al, 2011), and DHP also led to a decrease in the ratio of intracellular GSH/GSSG in cultured cells (Ishida et al, 2012). In addition, the exposure of cells to DHP led to the induction of antioxidant gene expression via the activation of the Nrf2-ARE pathway (Ishida et al, 2014).…”
Section: Resultsmentioning
confidence: 86%
“…The genotoxic 1,4,29) and cytotoxic 11,28,30) potentials of DHPs have been demonstrated previously. As stated earlier, the biological effects of DHPs are due to DHPs' dual capacity for high chemical reactivity and radical generation activity.…”
Section: +mentioning
confidence: 59%
“…In addition, cyclohexyl-DHP, which was designed according to our hypothesis of a relationship between the chemical structure of DHP derivatives and their DNA strand-cleaving activity (Maruoka et al, 2005), was shown to possess stronger DNA strand-cleaving activity than Me-DHP or Ph-DHP . More recently, it has been reported that the reaction of some Me-DHPs or cyclohexyl-DHP with GSH is a potential mechanism of bacterial growth inhibition (Takechi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%